ANALISIS KINERJA KARYAWAN DIVISI IT BERDASARKAN KEPUASAN DAN FLEKSIBILITAS KERJA - Mustakim, Masran; Sutoro, Moh.; Jamaludin, Pusporini Palupi (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The workload in technology and information is high, so demands for performance and productivity are inevitable. Especially in providing services, bringing quality is a must. The company, which is engaged in network and application development, is aware of this. In fact, this research was conducted to reveal information about the factors that influence the performance of employees in the field of technology and information. So that it can be stated the efforts to repair and increase it. To prove this, a quantitative approach was used, this was done so that it was easy to get data and could provide a picture that was easier to understand. The sample technique used is simple random, with the number of respondents 67. There is also a way to collect data, do the distribution of questionnaires. The data obtained, then analyzed with regression techniques. From the research results, it is known that an effective work model for improving the performance of IT employees is flexible working hours. This means that the type of IT work tends to spend a lot of time, so giving freedom in terms of working time is an effective way to increase morale and work productivity.